Microstructure and surface characterization of Ni-Cr based composites containing variable solid lubricants - Wan Farhana, Mohamad; Amir Azam, Khan; Pierre, Barroy; Oliver, Durand-Drouhin; Clement, Puille; Abdelilah, Lahmar; Faiz, Ahmad (Taylor & Francis Group, 2020)
Ni-Cr based composites with and without the addition of solid lubricants (MoS2, Ag and CaF2) were prepared by powder metallurgy method. The samples were sintered at 1200°C in flowing argon atmosphere for 1 h. The physical properties such as sintered density, relative density and porosity were studied. The microstructures and phase studies of the Ni-Cr based composites were conducted using SEM analysis while the hardness of the composites were measured by Vickers Micro Hardness Tester. The friction tests were conducted with ball on disc configuration following ASTM G-99-95a standard. The MoS2 solid lubricant provides best lubrication at room temperature which is demonstrated by a low friction coefficient compared to pure Ni-Cr composites (0.176 compared to 0.394). The SEM pictures of worn out showed into evidence plastic deformation, solid debris distribution, and filling of pores with solid lubricant phases. The time taken for stabilization of friction coefficient also varies with the type of solid lubricant. Dual and multiple addition of solid lubricants are also able to reduce the friction of coefficient compared to pure Ni-Cr composite. SEM analysis shows the spreading of solid lubricant/s during the sliding test to provide lubrication to both contacting metals.